Retrospective analysis of outcomes and complications after Korus hemiarthroplasty in elderly patients with neck femur fractures - Maniscalco, Pietro; Puma Pagliarello, Calogero; Ciatti, Corrado; Gattoni, Serena; Burgio, Valeria; Cauteruccio, Michele; Di Stefano, Giovanni; Quattrini, Fabrizio; Guerra, Giovanni; Polidoro, Federico; Raggini, Filippo; Belluati, Alberto; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background: Femoral neck fractures (FNF) is one of the most common traumatic events in elderly patients: the choice of an appropriate treatment is necessary to decrease the related mortality and to achieve the best possible outcomes. Nowadays, it is still debated whether or not to cement the stem in hemiarthroplasty and above all, which stem to use to best respect the integrity of the elderly bone. Methods: From January 2017 to December 2019, a bi-centric study utilizing prospectively collected databases of elderly patients with FNF treated with uncemented Korus stem hemiarthroplasty was performed. Patients were preoperatively classified according to ASA score. Patients’ clinical and X-ray follow-up was at 1, 3, 6, 12 months. Harris Hip Score (HHS) was used for analysed clinical improvement. On the X-rays, we analysed iatrogenic fractures, osteolysis area and radiolucent lines in the stem region during follow up. Results: 233 patients were identified. Median follow-up was 12 months. Over time, 51 patients died (21.88%). Mean age was 89,56 ± 6,25. 75 patients had ASA score of 2 (32.3%), 102 patients a score of 3 (43.7%), 56 an ASA score of 4 (24,0%). The main Harris hip score was 68,66 ± 8.53 at 1 month of follow-up, 71,74 ± 9.65 after 3 months, 72,50 ± 10.66 at 6 months and 75,61 ± 9.63 at 12 months control. Conclusions: Hydroxyapatite coated stem with an accurate design guarantee early fixation, good clinical and radiographic results, low rate of re-intervention and mortality rate and a satisfying return to pre-injury activities.